Container traffic: East African case - V. S. Golubeva; N. V. Shcherbinin (Вестник университета)
The article reveals the historical features of foreign trade and its transport support in the East African region. In the course of the study an analysis of the export-import cargo flows structure in East Africa both in the colonial period and at the present time has been carried out. The region infrastructure facilities, including seaports, have been considered, their attractiveness for investments and doing business has been taken into account. The current level of container line service for providing the foreign economic transactions transport component has been shown and the main East African ports by level of line service and container turnover have been identified. The main problems and opportunities for increasing East African trade supplies and their logistics services have been revealed.